2022
DOI: 10.1155/2022/8709591
|View full text |Cite|
|
Sign up to set email alerts
|

Educational Psychology Analysis Method for Extracting Students’ Facial Information Based on Image Big Data

Abstract: At present, most of the research on academic emotions focuses on the concept, current situation, and relevance. There are not many researches on the application of artificial intelligence-based neural network facial expression recognition technology in practical teaching. With reference to image-based big data, this research integrates the application of artificial intelligence facial expression recognition technology with the research on educational theory and applies information technology to the actual teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Facial expressivity plays a crucial communication role as it enables the rapid assessment of the emotional state of the other person in a conversation. In an educational setup like our interview trainer system, the affects that emerge during a learning process belong to a specific subset like frustration, boredom, confusion, and enjoyment 64 by which the learner's cognitive situation is conveyed. Monitoring the learner's facial expressions would help the instructor in shaping the course of the training by adjusting the pace of teaching or balancing the intensity of the provided content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial expressivity plays a crucial communication role as it enables the rapid assessment of the emotional state of the other person in a conversation. In an educational setup like our interview trainer system, the affects that emerge during a learning process belong to a specific subset like frustration, boredom, confusion, and enjoyment 64 by which the learner's cognitive situation is conveyed. Monitoring the learner's facial expressions would help the instructor in shaping the course of the training by adjusting the pace of teaching or balancing the intensity of the provided content.…”
Section: Discussionmentioning
confidence: 99%
“…63 Facial expressivity plays a crucial communication role as it enables the rapid assessment of the emotional state of the other person in a conversation. In an educational setup like our interview trainer system, the affects that emerge during a learning process belong to a specific subset like frustration, boredom, confusion, and enjoyment 64 Having all these in mind, we performed an exploratory analysis on the facial expressivity of the participants in the condition of RoboREIT where the audio-visual interaction was performed with an embodied robot. Our objective is to investigate whether participants exhibited facial expressions during their interaction with Nao and, if so, to examine any differences in the expression patterns among participants.…”
Section: Exploratory Analysismentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%